Localized Bone Loss Resulted from an Unlikely Cause in an 11-Year-Old Child - Bianca Tozi Portaluppe Bergantin; Daniela Rios; Daniela Silva Barroso Oliveira; Edmêr Silvestre Pereira Júnior; João Adolfo Costa Hanemann; Heitor Marques Honório (Case Reports in Dentistry)
Periodontal diseases have several causes, amongst them, by foreign bodies. In this case report, an 11-year-old child who lived in a rural area and has never been treated by a dentist presented an extensive horizontal bone loss and edema on the region of tooth 44. The diagnosis of foreign body was obtained after biopsy, since an elastic band around the middle of the root tooth was found. The elastic band was not radiopaque, and the patient did not inform that she found the elastic band on the floor of the school and introduced the tooth by herself. Based on the case reported, it is concluded that anamnesis and clinical and radiographic examination are fundamental strategies to obtain the diagnosis, but sometimes, especially in children, there may be inconsistencies that can be elucidated by a biopsy.